Chiral (SO)-N-(SO) Sulfoxide Pincer Complexes of Mg, Rh, and Ir: N-H Activation and Selective Sulfoxide Reduction upon Ligand Coordination - Locke, Harald; Herrera, Alberto Cesar; Heinemann, Frank Wilhelm; Linden, Anthony; Frieß, Sibylle; Schmid, Bernhard; Dorta, Romano (Organometallics, 2015)
Multigram quantities of the optically pure amino bis-sulfoxide ligand (S,S)-bis(4-tert-butyl-2-(p-tolylsulfinyl)phenyl)amine ((S,S)-3) are accessible by in situ lithiation of bis(2-bromo-4-tert-butylphenyl)amine (1) followed by a nudeophilic displacement reaction with Andersen's sulfinate 2. Deprotonation of (S,S)-3 with MgPh2 yields the magnesium amido bis-sulfoxide salt (S,S)-4 quantitatively. Metathetical exchange of (S,S)-4 with [RhCl(COE)(2)](2) affords the optically pure pseudo-C-2-symmetric Rh(I) amido bis-sulfoxide pincer complex mer-(R,R)-[Rh(bis(4-(tert-butyl)-2-(p-tolylsulfinyl)phenyl)amide)(COE)] (mer-(R,R)-5). This complex reacts with 3 equiv of HCl to give the facial Rh(III) complex fac-(S,R,R)-[Rh(bis(4-(tert-butyl)-2-(p-tolylsulfinyl)phenyl)amine)-Cl-3] (fac-(S,R,R)-6), in which one of the sulfoxide functions has been reduced to the sulfide and in which the resulting sulfoxide-sulfide-amine ligand is facially coordinated. The same complexes S and 6 form in a 1:2 ratio in a disproportionation reaction when [RhCl(COE)(2)](2) is treated with 2 equiv of neutral ligand 3. N-H activation is directly observed in the reaction of [IrCl(COE)(2)](2) with 3, affording the amido-hydrido-Ir(III) complex [Ir(bis(4-(tert-butyl)-2-(p-tolylsulfinyl)phenyl)amide)(Cl)(H)(COE)] (8).